Idiopathic Pulmonary Hemosiderosis in Adults: A Case Report and Review of the Literature. (18th July 2012) - Tzouvelekis, Argyris; Ntolios, Paschalis; Oikonomou, Anastasia; Koutsopoulos, Anastasios; Sivridis, Efthimios; Zacharis, George; Kaltsas, Kostantinos; Boglou, Panagiotis; Mikroulis, Dimitrios; Bouros, Demosthenes
Abstract : Idiopathic pulmonary hemosiderosis is a very rare condition rarely affecting adults and causing recurrent episodes of diffuse alveolar haemorrhage that may lead to lung fibrosis. Due to lack of pathognomonic findings, IPH diagnosis is established upon exclusion of all other possible causes of DAH in combination with specific pathologic findings revealing bland alveolar haemorrhage with absence of vasculitis and/or accumulation of immune complexes within lung parenchyma. Here we describe a rare case of idiopathic pulmonary hemosiderosis in an otherwise healthy 27-year-old Greek male patient with relapsing episodes of fever accompanied by general fatigue and discomfort. He was at this time point a light smoker and had been hospitalised once in the past for similar symptoms. His iron deficiency anemia coupled with chest high-resolution computed tomography and bronchoalveolar lavage revealed findings compatible with diffuse alveolar hemorrhage. After excluding all other sources of bleeding through extensive gastrointestinal workup and thorough immunologic profile, video-assisted thoracic lung biopsy was performed and the diagnosis of Idiopathic Pulmonary Hemosiderosis was established. Patient was treated with high doses of oral corticosteroids, leading to clinical response. We highlight the need for vigilance by the respiratory physician for the presence of DAH, a challenging, acute condition requiring early recognition along with identification of the underlying syndrome and appropriate treatment to achieve optimal results.